2022
DOI: 10.1128/msystems.00077-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evidence for the Recycling of Complex Organic Carbon by Novel Thermoplasmatota Clades in Deep-Sea Sediments

Abstract: Deep oceans receive large amounts of complex organic carbon and anthropogenic pollutants. The deep-sea sediments of the continental slopes serve as the biggest carbon sink on Earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 105 publications
0
1
0
Order By: Relevance
“…In this study, the abundance of Thermoplasmatota increased under chlorinated hydrocarbon stress (Figure 3A), which has previously been reported to be related to the degradation of microplastics [50] and aromatics [51]. LEfSe analysis shows that Thermoplasmata, Methanomassiliicoccales, and Nitrosopumilaceae were enriched in the high concentration group (Figure 4A).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the abundance of Thermoplasmatota increased under chlorinated hydrocarbon stress (Figure 3A), which has previously been reported to be related to the degradation of microplastics [50] and aromatics [51]. LEfSe analysis shows that Thermoplasmata, Methanomassiliicoccales, and Nitrosopumilaceae were enriched in the high concentration group (Figure 4A).…”
Section: Discussionsupporting
confidence: 79%
“…However, samples from Prachuap Kiri Khan Province (NHH) showed Thermoplasmatota in high abundance rather than Bacteroidota. Thermoplasmatota is a novel group of archaea found primarily in surface seawater and is potentially involved with the ocean carbon cycle [ 32 ]. The result showed that Proteobacteria was negatively correlated to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The sulfur oxidation capacity of SOB MAGs belonging to Bacteroidia , Marinisomatota , Chloroflexota, and Actinobacteriota was identified in other environments such as seafloor sulfide deposits, OMZs, groundwater, and geothermal environments ( 68 71 ). The archaeal MAG185 belongs to Thermoplasmatota and its potential sulfide-oxidizing capacity has been found in the novel Thermoplasmatota clade from deep-sea sediments ( 72 ). DsrEFH can act as an effective sulfur donor for DsrC to participate in the sulfur oxidation process, and genes encoding DsrEFH were annotated in several SOB MAGs ( 73 ).…”
Section: Discussionmentioning
confidence: 99%